METHODOLOGICAL PROVISION OF CALCULATING THE PRICE OF PRODUCTS IN FRUIT AND ITS IMPROVEMENT - Tursunkulova Gulchiroy Burkhonovna (Scholar Express Journals, 2024)
The article describes the issues of methodical support for calculating the cost of products in fruit growing. Normative legal documents on further development of horticulture have been studied. Economists' approaches to product costing have been studied. Calculation methods for determining the cost of fruit products are recommended.
Keywords: fruit growing; products; accounting